2015
DOI: 10.5137/1019-5149.jtn.13884-14.2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of adult reducible atlantoaxial dislocation, basilar invagination and chiari malformation with syringomyelia

Abstract: ABSTRACTand nervous elements within this region, any congenital malformation of one tissue may cause a wide spectrum of neurological deficit, especially the compression of medulla oblongata, which may lead to serious consequences.Appropriate and timely diagnosis and treatment of these malformations are of great significance. However, there is still lack of an ideal method to cure all of these malformations. Anterior transoral decompression at the CVJ can occur in many types of pathology, including malformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Although pediatric neurosurgeons tend to favor bony decompression for Chiari I malformations, leaving the dura intact to avoid CSF-related complications, the rates for postoperative syrinx decreases are lower with this technique compared with those involving duraplasty. 32 In basilar invagination, the rates for postoperative syrinx reductions achieved with posterior realignment and fusion alone are disappointing, with reported rates of 28.1% 9 and 31.6%, 33 whereas rates of 71.4%, 28 80%, 34 and 92.3% 35 have been obtained with additional foramen magnum decompressions including duraplasty. In the present study, syringomyelia was either reduced or stabilized in 93.3% of patients with this technique.…”
Section: Syringomyeliamentioning
confidence: 99%
“…Although pediatric neurosurgeons tend to favor bony decompression for Chiari I malformations, leaving the dura intact to avoid CSF-related complications, the rates for postoperative syrinx decreases are lower with this technique compared with those involving duraplasty. 32 In basilar invagination, the rates for postoperative syrinx reductions achieved with posterior realignment and fusion alone are disappointing, with reported rates of 28.1% 9 and 31.6%, 33 whereas rates of 71.4%, 28 80%, 34 and 92.3% 35 have been obtained with additional foramen magnum decompressions including duraplasty. In the present study, syringomyelia was either reduced or stabilized in 93.3% of patients with this technique.…”
Section: Syringomyeliamentioning
confidence: 99%
“…Occipital/neck pain was reported in seven articles: 192 of 328 patients (58.5%) had symptoms of occipital/neck pain. 4 , 5 , 7 , 12 , 15 , 19 , 20 In the six articles that reported paresthesias, 221 of 307 patients (72.0%) were affected. 4 , 5 , 7 , 12 , 15 , 19 Five articles reported weakness.…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 11 Studies have reported success with anterior decompression and transoral approaches, posterior decompression with or without instrumentation, craniocervical fusion, and C1/C2 joint distraction and fixation. 12 , 13 , 14 , 15 , 16 The literature on the treatment for CM-CVJA is heterogeneous; varying populations, interventions, and measured outcomes render it difficult to claim an ideal method. We therefore sought to systematically review the literature to evaluate the trends and outcomes of surgical interventions for patients with CM-CVJA abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Следует отметить, что в литературе, посвященной анализу методик фиксации, не расставляются подобные акценты (по протяженности, локализации и нозологии) [8,9,17], что подтверждает оригинальность полученных данных. Реализация этих преимуществ осуществляется только посредством непременного использования винтовой фиксации [17], которая является относительно более безопасной, даже при наличии мальпозиций элементов металлоконструкции [14,15]. Следует отметить, что, по нашим данным, задняя стабилизация имеет более низкое соотношение осложнений, в том числе имплантатозави-симых, с необходимостью ревизионных вмешательств для их устранения [18,19].…”
Section: Discussionunclassified